Fulfilment of Accessibility Rights For Persons With Disabilities In Class IIA Correctional Institutions In Parepare City - Yunus, Muhammad Kemal; Purwanda, Sunardi; Saputra, Iswandy Rani; Sabir, Muhammad; Kairuddin, Kairuddin (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study aims to analyze the implementation of accessibility rights fulfillment for inmates with disabilities at the Class IIA Correctional Institution in Parepare City. Persons with disabilities are a vulnerable group requiring special treatment in accordance with human rights principles and national regulations, such as Law Number 8 of 2016 concerning Persons with Disabilities and Law Number 22 of 2022 concerning Corrections. This research employs a normative-empirical method with a statutory and social approach through literature study, observation, and direct interviews with prison officials and inmates with disabilities. The results show that the Class IIA Correctional Institution in Parepare has taken significant steps to fulfill accessibility rights, such as providing special shuttle services, rooms with sitting toilets, separation of inmates with disabilities, intensive care, and wheelchair facilities. In addition, there is collaboration with the Health Office, Ministry of Social Affairs, and other agencies to support optimal services. However, there are still shortcomings, such as the unavailability of hearing aids for inmates with hearing impairments. In general, the Class IIA Correctional Institution in Parepare demonstrates a commitment to providing inclusive and non-discriminatory services, including the right to interact with other inmates. These findings highlight the importance of continuous improvement to create a disability-friendly correctional environment.